2015
DOI: 10.1007/s00216-015-9169-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of phosphatidylethanol 16:0/18:1, 18:1/18:1, and 16:0/16:0 in venous blood and venous and capillary dried blood spots from patients in alcohol withdrawal and control volunteers

Abstract: To refer to or to cite this work, please use the citation to the published version:Kummer N., Ingels A-S., Wille S. M.R., Hanak C. , Verbanck P. , Lambert W., Samyn N., Stove C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 34 publications
4
33
1
14
Order By: Relevance
“…Research staff in our study were trained by a short instructional video on collection. PEth levels from one study demonstrated consistency in measurements between capillary-DBS, whole blood, or venous-DBS (Kummer et al, 2016) allowing for multiple routes of blood collection, and PEth can be assayed as soon as 60 minutes after alcohol consumption (Gnann et al, 2012). Finally, unlike whole blood venipuncture, PEth does not continue to increase after DBS collection in individuals that had an elevated BAC at time of blood draw (Schrock et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research staff in our study were trained by a short instructional video on collection. PEth levels from one study demonstrated consistency in measurements between capillary-DBS, whole blood, or venous-DBS (Kummer et al, 2016) allowing for multiple routes of blood collection, and PEth can be assayed as soon as 60 minutes after alcohol consumption (Gnann et al, 2012). Finally, unlike whole blood venipuncture, PEth does not continue to increase after DBS collection in individuals that had an elevated BAC at time of blood draw (Schrock et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…DBS proved to be advantageous concerning the analyte's stability: While the DBS is drying, enzymatic activity is stopped and ethanol evaporates, preventing metabolic post‐sampling formation or degradation of PEth . Furthermore, the possibility of minimally invasive fingertip sampling to obtain capillary DBS has attracted research attention . Contrary to the blood sampling by venipuncture, healthcare professionals such as nurses or doctors are not needed for the capillary DBS sampling.…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, the possibility of minimally invasive fingertip sampling to obtain capillary DBS has attracted research attention. 12 Contrary to the blood sampling by venipuncture, healthcare professionals such as nurses or doctors are not needed for the capillary DBS sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Also in the context of driving license regranting programs, in which drivers with a history of alcohol abuse are followed up, DBS sampling may be beneficial. We recently demonstrated this for phosphatidylethanol (PEth), a direct alcohol marker that is used to monitor alcohol consumption during the past few weeks: capillary concentrations of PEth were equivalent to those found in venous blood, demonstrating that capillary DBS are a valid alternative for venous blood for this purpose 66 . Since the sampling procedure does not require dedicated staff and PEth outperforms indirect markers like carbohydrate-deficient transferrin (CDT), capillary DBS sampling offers a promising avenue for routine follow-up of drivers with a history of alcohol abuse.…”
Section: Toxicologymentioning
confidence: 99%